SUMBANGSIH PEMIKIRAN MU’TAZILAH DI INDONESIA - Dafirsam; Nunu Burhanuddin (MUSHAF JOURNAL: Jurnal Ilmu Al Quran dan Hadis, 2023)
This article discusses the contribution of Mu'tazilah thought in the context of Islam in Indonesia. Kalam science or the study of theology is in the spotlight in discussing divine concepts in Islamic teachings. The author reviews the role of the Mu'tazilah as one of the schools that uses rationality in Islamic theological thought, examining the five main principles in their teachings: monotheism, God's justice, promises and threats, the position between two positions, and amar makruf nahi ungkar. The research method uses literature study with a critical descriptive approach. The results reveal the contribution of the Mu'tazilah to Islamic thought in Indonesia, with an emphasis on the concepts of monotheism, God's justice, promises and threats, as well as their important role in modern thought. Mu'tazilah thought is also associated with its influence on Indonesian thinkers, such as Harun Nasution, who fought for the renewal of Islamic thought and an emphasis on rationality in understanding religion. The implications of Mu'tazilah thought include efforts to build rational awareness in the Islamic religion, reinvigorate ijtihad, educational reform, and changes in political structures. The conclusion is that the Mu'tazilah understanding of rationality has made an important contribution to Islamic thought in Indonesia, strengthening an inclusive and open thinking approach to developments of the times and science.